A nudge to quit? The effect of a change in pension information on annuitization, labor supply and retirement choices among older workers - Johannes Hagen; Daniel Hallberg; Gabriella Sjögren Lindquist (Global Labor Organization (GLO), 2018)
Nudge is about affecting behavior in a certain way through small changes to the choice architecture. However, a nudge may also affect behaviors that the architect did not intend. We show that such spillover effects exist in a highly policy relevant context where the use of nudge is widespread; retirement. Specifically, we find that an exogenous application form change in the Swedish pension system that highlighted a five-year payout on the expense of a life annuity not only increased the demand for the nudged payout (as expected), but also induced individuals to retire earlier. We attribute the effects to decision-framing.
Keywords: D91; G41; J26; J32; 330; annuity; pension; nudge; decision framing